Social Interaction and Prosocial Behavior Through the Lens of Social Psychology - Dirga, Refan; Mukhtar, Alif; Alfarid, Reza (Journal Social Humanity Perspective, 2024)
This paper examines the process by which social interaction acts as a social catalyst to prosocial behavior; the analysis of this paper will be based on the concept of social psychology and within the discipline of management. The study employs a qualitative method to examine the relational processes involved in empathy, reciprocity, group belonging, and trust and limits to cooperative behavior through barriers of conflict, prejudice, and mistrust. The information was gathered through the intensive interviews of the respondents at both organizational and community levels and it was found out that PR sociality is not a characteristic of individuals but a socially based phenomenon created in the process of continuing communication. The results reveal that, in case a sense of empathy and emotional bonding is created through social interaction, people are more ready to offer assistance beyond their self-immediate selfishness. Reciprocity and mutual obligation are the forces of stability that support the prosocial behavior and shared identity reinforces collective orientation and cooperation. On the other hand, war and discrimination disintegrate social ties, and the absence of trust limits the desire to participate in the helping actions. The work brings to the management literature the repackaged meaning of PR sociality as a strategic capital as opposed to an accidental by-product of organizational existence. The implications it brings out paint a picture to show that leaders and managers should be vigilant enough to create an environment that fosters trust, inclusivity, and a sense of shared belonging to achieve the performance advantages of prosocial behavior. With the ability to combine the social psychology of understanding management into the discourse, this research presents the significance of social processes at the micro-level in the determination of macro-level organizational outputs, which not only provides a theoretical enrichment to the field, but also practical advice on the establishment of robust collaborative structures.